Predictors of Bilateral Disease in Low-Risk Papillary Thyroid Cancer: Histopathologic Insights and Preoperative Ultrasonography - Rodriguez Schaap, P. M.; Papachristos, A.; Serrao-Brown, H.; Aniss, A.; van Dijkum, E. J. M. Nieveen; Gill, A. J.; Delbridge, L.; Engelsman, A. F.; Sidhu, S.; Sywak, M. (Annals of surgical oncology, 2025)
Background With the current shift toward de-escalation of surgical management in low-risk papillary thyroid cancer (PTC), understanding predictors and the clinical significance of additional tumors in the contralateral lobe is important. This study investigated the histopathologic predictors of bilateral disease in low-risk PTC patients and the utility of preoperative ultrasonography in guiding completion thyroidectomy decisions. Methods Patients treated with total thyroidectomy (TT) for low-risk PTCs (< 4 cm) at the Endocrine Surgical Unit of the Royal North Shore Hospital, University of Sydney from 2013 to 2020 were identified from a prospectively maintained database. The primary objective was to evaluate whether specific histopathologic factors can reliably predict the likelihood of bilateral disease in low-risk PTC patients after hemithyroidectomy. The secondary objective was to assess the accuracy of preoperative ultrasonography for patients with bilateral disease. Results Of the 737 patients in this study, 194 (26.3%) had bilateral disease. The multivariate analysis showed that larger median tumor size (odds ratio [OR] 1.043 per mm; 95 % confidence interval [CI] 1.025–1.062; P < 0.001), ipsilateral multifocal disease (MFD) (OR 2.010; 95% CI 1.338–3.020; P < 0.001), and venous invasion (OR 1.693; 95% CI 1.058–2.707) had a significant association with bilateral disease. However, in the prediction of clinically significant contralateral disease (≥ 10 mm), median tumor size (OR 1.104 per mm; 95% CI 1.059–1.152; P < 0.001) and venous invasion (OR 2.815; 95% CI 1.044–7.589; P = 0.041) were significantly correlated, whereas ipsilateral MFD lost its significance. These significant contralateral tumors were identified preoperatively and associated with higher Thyroid Imaging, Reporting and Data System (TIRADS) and/or Bethesda cytology classifications in 94% of cases. Conclusion In low-risk PTC patients, larger tumor size, venous invasion, and ipsilateral MFD are significantly associated with disease in the contralateral thyroid lobe.